Potential antibacterial activity of Botryosphaeria rhodina: Mangrove Xylocarpus granatum J. Koenig. derived fungal endophyte - Tetty Marta Linda, Rudi Hendra, Analdi Farniga, Noviza Delfira, Friardi Ismed, Yuli Haryani (Journal of Applied Pharmaceutical Science, 2024)
Exploring the secondary metabolites with excellent biological activity and pharmacy value from mangrove-derived fungi has attracted great attention. This study aims to isolate endophytic fungi that exhibit antimicrobial activity from Mangrove plants in Siput River Estuaries, Bengkalis Regency, Riau Province, Indonesia. Fifteen isolates of fungal endophytes have been isolated from the root of different Mangrove species, i.e., Aegiceras sp., Lumnitzera racemosa Wild., Avicennia marina (Forssk.) Vierh., Laguncularia racemosa (L) C. F. Gaertn., Sonneratia ovata Backer., Kandelia candel (L) Druce., and Xylocarpus granatum J. Koenig. In vitro, antagonism test was performed for all isolated endophytes against selected pathogenic bacteria. Ten of fifteen endophytes were able to inhibit at least one pathogen with a diameter of inhibition zones ranging from 7,62 ± 0,55 to 18,20 ± 0,98 mm. Three fungi (F15, F2, and F5) with the highest antibacterial activity were subjected to molecular characterization based on the ribosomal region of the internal transcribed spacer by PCR amplification using ITS4 and ITS5 primers. The most potential isolate (F15 from Xylocarpus granatum J. Koenig) showed 99.82% similarity with Botryosphaeria rhodina isolate P130. Its ethyl acetate extract was found positive for terpenoid, phenolic, and flavonoid presence. F2 and F5, originated from L. racemosa Wild. and Avicennia marina (Forssk.) Vierh., had 100% similarity with Fusarium equiseti isolate FUS-34-2 and Aspergillus fumigatus strain DTO 402-H1, respectively. All endophytic fungi are recorded for the first time in Riau Mangrove.
Keywords: Botryosphaeria, antibacterial, fungal endophytes, mangrove